WDM for multi‐user indoor VLC systems with SCM. Issue 18 (1st November 2019) - Younus, Safwan Hafeedh; Al‐Hameed, Aubida A.; Hussein, Ahmed Taha; Alresheedi, Mohammed T.; Elmirghani, Jaafar M.H.
Abstract : A system that employs wavelength division multiplexing (WDM) in conjunction with sub‐carrier multiplexing (SCM) tones is proposed to realise high data rate multi‐user indoor visible light communication (VLC). The SCM tones, which are unmodulated signals, are used to identify each light unit, to find the optimum light unit for each user and to calculate the level of the co‐channel interference (CCI). WDM is utilised to attain a high data rate for each user. In this study, multi‐colour (four colours) laser diodes are utilised as sources of lighting and data communication. One of the WDM colours is used to convey the SCM tones at the beginning of the connection to set up the connection among receivers and light units (to find the optimum light unit for each user). To evaluate the performance of the VLC system, two types of receivers are proposed: an array of non‐imaging receivers and an array of non‐imaging angle diversity receivers. In this study, the effects of diffuse reflections, CCI and mobility on the system performance are considered.